Clinical Evaluation of Autologous Small Blood Stem Cells in Guided Bone Regeneration for Dental Implant Placement: A Phase I Study - Mehwish Urooj; Asma Siddiqui; Affan Ahmed; Muhammad Khawaja Hammad Uddin; Ayesha Akram; Qudsia Sabhi (Pakistan Journal of Medicine and Dentistry)
Background: Autologous small blood (SB) stem cells, a new stem cell subtype present in the peripheral blood of adults, were found to exhibit regenerative capacities in bone regeneration. This phase I clinical study aimed to study SB cells' safety, tolerability, and early efficacy in guided bone regeneration (GBR) surgical procedures in cases of severe alveolar bone defects among patients who are to receive a dental implant.